Den melankolske naturlighed: Henrik Pontoppidans "Bonde-Idyl" (1883) - Michaëlis, Bo Tao (Pontoppidaniana, 2025)
Abstract: The Melancholy Nature Henrik Pontoppidan’s 1883 novella Bonde-Idyl is, in many ways, captivating. It stands as an early example of Danish Naturalism in the French tradition of Émile Zola and others – where everything that exists is seen as part of nature, including man. Humanity is not the creation of a supernatural deity but, following the theories of Charles Darwin, a complex mammal – a human beast – driven more by lust and desire than by reason. With its ironically idyllic title, the story centres on human sexuality as the driving force behind the repetition of a natural pattern of power. What I term the melancholy nature refers to the circular way nature repeats itself in a gloomy cycle that prohibits real change. The survival of the fittest here appears in a modernised version of jus primae noctis (the lord’s right to the first night with a new bride) transformed into the rural gentry’s systemic abuse of lower-class women. The novella is the work of a disillusioned romantic, for whom even the moon sighs at the end.